2016
DOI: 10.1016/j.antiviral.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of baculovirus in chickens: How it modifies the immune response against infectious bursal disease virus

Abstract: Several reports have shown that baculoviruses (BVs) have strong adjuvant properties on the mammalian immune system. Recent studies of our group demonstrated the ability of BV to stimulate the innate immunity in chickens. In this investigation, we aimed to assess the potential antiviral effect of BV given both, before and after infectious bursal disease virus (IBDV). In the first case, specific pathogen free chickens were intravenously inoculated with 5 × 10(7) pfu of Autographa californica nuclear polyhedrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…This result was similar to other reports which showed the correlation between high level of virus replication and intense inflammatory response caused by genotype VIId NDV in chickens and ducks ( Ecco et al, 2011 ; Rue et al, 2011 ; Rasoli et al, 2014 ; Hu et al, 2015 ; Kang et al, 2015 ). The present findings are also in agreement with the observations in chickens infected by other avian viruses, including avian influenza virus ( Lee et al, 2013 ; Guan et al, 2015 ), infectious bursal disease virus ( Chimeno et al, 2016 ), and laryngotracheitis virus ( Vagnozzi et al, 2016 ). Taken together, these results demonstrated that NDV infection induced strong innate immune responses and intense inflammatory responses at early stage in goose.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result was similar to other reports which showed the correlation between high level of virus replication and intense inflammatory response caused by genotype VIId NDV in chickens and ducks ( Ecco et al, 2011 ; Rue et al, 2011 ; Rasoli et al, 2014 ; Hu et al, 2015 ; Kang et al, 2015 ). The present findings are also in agreement with the observations in chickens infected by other avian viruses, including avian influenza virus ( Lee et al, 2013 ; Guan et al, 2015 ), infectious bursal disease virus ( Chimeno et al, 2016 ), and laryngotracheitis virus ( Vagnozzi et al, 2016 ). Taken together, these results demonstrated that NDV infection induced strong innate immune responses and intense inflammatory responses at early stage in goose.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we selected IFN-γ, IL-1β, IL-8, IL-2, IL-6, and IL-18 as indicators of antiviral and proinflammatory responses. These cytokines have been studied to understand the host immune response to a wide range of avian viruses and are important in infection control and virus clearance in birds ( Ecco et al, 2011 ; Rue et al, 2011 ; Lee et al, 2013 ; Rasoli et al, 2014 ; Guan et al, 2015 ; Kang et al, 2015 ; Chimeno et al, 2016 ). The cytokine gene analysis showed that NDV infection in geese increased expressions of IFN-γ, IL-8, and IL-18.…”
Section: Discussionmentioning
confidence: 99%